Case Report: A case of PLA2G6 gene-related early-onset Parkinson's disease and review of literature - Gao, Lili; Shi, Chunlan; Lin, Qing; Wu, Yujing; Hu, Liqi; Wang, Mingwang; Guan, Jianhua; Lin, Sheng; Liao, Yuansheng; Wu, Chenghan (Frontiers in Neuroscience, 2022)
Background: Early onset Parkinson's disease (EOPD) is a neurodegenerative disease related to genetic factors. A mutated phospholipase A2 type VI gene (PLA2G6) is considered to be one of pathogenic genes involved in EOPD development. Although EOPD caused by a mutated PLA2G6 has been recorded in major databases, not all mutant genotypes have been reported. Here, we report a case of PLA2G6--related EOPD caused by a novel compound heterozygous mutation. Case presentation: The case was a of 26-year-old young male with a 2-year course of disease. The onset of the disease was insidious and developed gradually. The patient presented with unsteady walking, bradykinesia, unresponsiveness, and decreased facial expression. Auxiliary examination showed a compound heterozygous mutation of the PLA2G6gene with c.991G > T and c.1427 + 1G > A. Cranial MRI revealed mild atrophy of the cerebrum and cerebellum. The patient was diagnosed with EOPD. We administered treatment with Madopar, which was effective. After two-year disease course, we observed progression to stage 5 according to the Hoehn-Yahr Scale (without medicine in the off-stage). An MDS-UPDRS III score of 62 was obtained, with characteristics of severe disease and rapid progress. The diagnosis was a EOPD phenotype caused by a combination of mutations at the c.991G > T and c.1427 + 1G > A sites of the PLA2G6gene. Conclusions: After active treatment, the disease was set under control, with no significant progression during the three-month follow-up period. Dyskinesia did not recur after reducing the Madopar dose. The freezing sign was slightly decreased and the wearing-off was delayed to two hours.